Improvement of Surface Properties of Prosthetic Implants through TiO2 by Using Dip Coating Method - Aboud, Wajdi Sadik; Hamdi, Dunya Abdulsahib (International Journal of Engineering and Technology, 2018)
In this research, the dip coating method is used to prepare the Ti-6Al-4V alloy by powder ceramic titania (TiO2 of 50 nm particle size) in order to improve the biocompatibility of the alloy surface for implant applications. Atomic Force Microscopy, Optical microscope, X-ray diffraction, and Scanning Electron Microscopic are performed to describe the phases and microstructure of alloy surface. Moreover, the In vitro test was performed to investigate the morphology of the alloy surface in simulated body fluid solution before and after the coating process. The experimental results of the Atomic Force Microscopy showed that the coated particles film is still with a nano-size of 90 nm. Furthermore, the X-ray diffraction outcomes showed that the TiO2 is within the retail phase, very visible, and fully coated with high intensity of plane (110). The optical microscope is clearly showed that the grain boundary is reduced with increasing the film thickness. The Scanning Electron Microscopic images are clarified that the alloy is completely coated by TiO2. Additionally, no crack appeared within the coated film and the aggregations are formed with a size of 300 nm. The results of the in vitro test for the coated samples are shown the following advantages; the values of corrosion potential (Ecorr) were shifted towards the positive direction of the potential, the values of corrosion current density (Icorr)Â  were reduced to be more negative as well as the Corrosion Rate CR is also reduced accordingly.